Workforce neurodiversity and workplace avoidance behavior: The role of inclusive leadership, relational energy, and self‐control demands - Iqbal, Qaisar; Volpone, Sabrina D.; Piwowar‐Sulej, Katarzyna (Human Resource Management, 2025)
AbstractWe draw on job demands‐resources theory to develop and test a model that explores the direct and indirect (through relational energy) impact of inclusive leadership on workplace avoidance behaviors for neurodivergent employees. We also examine the moderating role of personal self‐control demands in the relationship between relational energy and workplace avoidance. We tested our model using partial least square ‐ structural equation modeling analysis with data collected using a time‐lagged data collection in a sample of 215 neurodiverse employees working in multinational companies across the Gulf Cooperation Council region (i.e., Saudi Arabia, United Arab Emirates, Oman). The findings demonstrate that inclusive leaders mitigate workplace avoidance behavior in neurodivergent employees. That is, inclusive leaders create an environment that contributes to the cultivation of employees' personal relational energy resources. Then, high levels of relational energy interact with employees' level of personal demands (i.e., impulse control, resisting distractions) to reduce workplace avoidance behaviors. Our work speaks to the integrated role of demands and resources in workplaces that can thwart avoidance behaviors for neurodivergent employees.